Assessing compatibility, tansesterification, and disintegration of PET/PLA fiber blend in composting conditions - Kheirandish, Maryam; Mohaddes Mojtahedi, Mohammad Reza; Nazockdast, Hsossein (Frontiers in Materials, 2023)
To recycle a mixture of PET and PLA, understanding the challenging issues and crucial parameters that affect the properties and morphology of the blend is key to successful recycling. So, the main focus of this study was to investigate the parameters that influence the processability, compatibility, morphology, properties, and disintegration of PET/PLA blend fibers. Using surface tension measurements, acceptable adhesion between the two components was observed. SEM results showed that the PET/PLA blend fibers have a microfibrillar morphology. Based on 1H NMR analysis, the exchange reaction resulted in a block copolymer. The crystallization process in the fibers became more difficult as the PLA content increases due to the formation of copolymers through transesterification. The presence of oriented crystals in the melt-spun fiber blend was confirmed by X-ray diffraction patterns. As the PLA content increased, the tensile strength of blends decreases gradually. Furthermore, the sample containing 20 wt. % PLA exhibited the highest dimensional stability. The disintegration process in composting conditions of PET was improved by PLA.